Palladium‐Catalyzed Deformylation Reactions with Detailed Experimental and in Silico Mechanistic Studies. Issue 28 (31st July 2017) - Modak, Atanu; Rana, Sujoy; Phukan, Ashwini K.; Maiti, Debabrata
Abstract : A facile, efficient, and general deformylation reaction with a wide‐ranging functional group compatibility has been developed with palladium acetate as a precatalyst under exogenous ligand‐free conditions. The mechanistic details of the palladium‐catalyzed deformylation reaction have been outlined on the basis of a combination of experimental and computational studies. The heterogeneous pathway is predominant for the deformylation, and homogeneous catalysis occurs to a lesser extent. This ligand‐free catalytic cycle is proposed to undergo oxidative addition, migratory extrusion, and reductive elimination as the key steps. Kinetic studies reveal a first‐order rate dependency with respect to the aldehyde. Furthermore, kinetic isotope effects, competition experiments, and Hammett studies suggest that the migratory extrusion step is the rate‐determining step. For the homogeneous pathway, the experimental findings are also supported by DFT studies. Abstract : The mechanistic details of palladium acetate catalyzed deformylation reactions are outlined herein. On the basis of kinetic studies, competition experiments, and a Hammett study, a plausible catalytic cycle is proposed. From heterogeneity tests, the existence of homogeneous and heterogeneous pathways is suggested. DFT calculations also support the catalytic pathway under homogeneous conditions.